Investigating the Effects of Tourism and Remittance Inflow on Economic Growth in Nigeria - Ojonta, Obed I.; Eze, Chikodili; Nebo, Ifeanyi Kennedy; Eze, Afamefuna Angus (Unisia, 2024)
The importance of economic growth in stimulating the overall production of goods and services cannot be overemphasized. The tourism sector and remittance inflow have been found to be relevant factors in explaining Nigeria's economic growth dynamics. To this end, this study focuses on investigating the effects of tourism and remittance on economic growth in Nigeria. The present study is different from the existing studies in two ways. First, this study employed the ordinary least square technique and dataset from 1981 to 2021. Second, our study adopted two variables: personal remittances and number of tourism arrivals. These variables were used to measure remittance inflow and tourism. The study revealed that tourism and remittance inflow are positive and significantly impact economic growth in Nigeria. This suggests that tourism and remittance inflow offer important channels for promoting economic growth. Hence, the policy recommendations from this study are based on our findings.